Insight of phylogeny and the number of sporangium annulus cells in Coniogramme ser. Coniogramme - Wang, Cai-Hong; Yang, Wen-Li; Zhang, Dan-Ke; Zhang, Gang-Min (Phytotaxa, 2020)
Coniogramme ser. Coniogramme is a perennial herbaceous fern group of the subfamily Cryptogrammoideae in Pteridaceae. The phylogenetic reconstruction of this series was performed using five chloroplast markers (matK/psbA-trnH/rbcL/rps4-trnS/trnL-F). The sporangium annulus cell numbers of eight species have also been counted and statistically assessed. The results showed that the present defined C. ser. Coniogramme is not a monophyletic group. Coniogramme merrillii, which has the highest number of annulus cells (median 18), is sister to the other species of this genus, and the number of sporangium annulus cells is stable at the species level and of great phylogenetic significance. It is not supported by both molecular and morphological evidence to synonymize C. merrillii, C. petelotii and C. gigantea in C. fraxinea. C. merrillii should be treated as a synonym of C. macrophylla, while C. lanceolata be accepted as a distinct species.